(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
The dielectric properties measurements of some dielectric materials, used in microwave and millimeter wave technology, are performed in F band (90-140 GHz) by using free space technique. A system, which consist a Performance Network Analyzer, two pyramidal horn antennas, a quasi-optical bench and an in house developed code TTDS are used in measurements. The measurement results are also verified by the simulation results obtained by CST-Microwave Studio